Evaluation of a competition wheelchair based on estimation of muscle activity for forward linear operation by using inverse dynamics analysis - Kobayashi, Y.; Tanaka, K. (Proceedings, 2018)
The objective of this study was to evaluate an optimum structure for a rugby wheelchair by estimating the muscle force during forward linear operation of the wheelchair using an inverse dynamics analysis. The simulation model was represented by restraining the contact area between the frame and seat of the wheelchair and the body model. Three body model variations were constructed with different degrees of disability. Wheelchair models were also constructed by varying the range of camber angle, wheel diameter and axle positions, respectively. The effects of the design parameters for the wheelchair on the muscle force were investigated. As a result, the axle position had the strongest effect on the muscle force of the upper limbs, and it is effective to lower the axle position for reducing the muscle force required. This implies that the adjustment of the axle position leads to a reduction in risk of injury occurrence.